TECHNOLOGY OF NEW EXTRACTION OF LIQUID HYDROCARBONS IN MINES (American Journal of Research in Humanities and Social Sciences, 2024)
Due to satellite oil gases, global warming, acid residues, climate change and the strengthening of the greenhouse effect are taking place.If we take into account that 60 billion m3 of gas is produced in Uzbekistan for a year, 58.4% of it is sent for domestic use, 6.5% to underground storages, 12.5% to the cycling process and 22.5% to export. . If 3% of the total recoverable gas is released into the atmosphere through a flare, it makes a big indicator.If we take into account that burning 1000 m3 of satellite oil gas releases 3 tons of carbon dioxide into the atmosphere, then burning 1.5 billion m3 of gas releases 4.5 million tons of carbonic acid into the atmosphere. Of the 60 billion cubic meters of satellite oil gas produced in Russia, 20 billion cubic meters of gas is burned by flares, and the remaining 40 billion cubic meters of gas is used for the company's needs, a large volume of gas is used for electricity generation, 3 billion cubic meters for processing and gas chemistry. .m3 of raw material, a small amount of raw material is pumped into the layer.